Le silence du peuple: the rhetoric of silence during the French Revolution - Jung, Theo (2017)
Abstract: In July 1789, a phrase was introduced into French political discourse that would quickly become a standing expression: le silence du peuple est la leçon des rois. Taking this political bon mot as a starting point, the article traces the uses of and responses to collective silences during the French Revolution. It is argued that silence cannot be reduced to just the lack of ‘voice’ indicating suppression or political impotence. Rather, it must be understood as a mode of political action with a rhetoric of its own. Sketching this rhetoric not only highlights the nature and functions of a mode of political communication too often disregarded. It also shows how the controversies surrounding these silences reflected some of the major political questions of the day, playing a key role in the renegotiations of the communicative spaces of politics set off by the Revolution